The band gap and nonlinear optical susceptibility of SrSn1-xVxO3 films - Huang, Ziheng; Ma, Qiushuang; Wang, Depeng; Zhao, Rongjing; Niu, Ruifeng; Wang, Weitian (Frontiers in Materials, 2024)
Perovskite-type oxide SrSn 1-x V x O 3 thin films with different concentrations x = 0.1~0.9 were fabricated by using pulsed-laser deposition, and the effects of V doping on the structure, optical band gap and the third-order optical nonlinearity were systematically investigated. With the increase of x value, the lattice parameters of SrSn 1-x V x O 3 decrease from 3.997 to 3.862 Å gradually, while the optical band gaps firstly increase and then decrease with boundary at x = 0.3. The third-order nonlinear optical responses were studied via the z-scan technique. The closed-aperture measurements show a negative nonlinear refractive index n 2 , and the open-aperture measurements demonstrate a saturable absorption β. Both the n 2 and β responses vary with the increase of V doping level. The metal-oxygen chemical bond along with the localized V 5+ Sn 2+ V 5+ complex contribute to the enhancement of optical nonlinearity, and the highest value of third-order susceptibility χ (3) is observed in SrSn 0.5 V 0.5 O 3 film.